KETAKUTAN, PERAN INVESTOR INSTITUSI DAN PERILAKU HERDING DALAM FASE PANDEMI COVID 19 - Fenny Marietza; Nikmah Nikmah; Fitrawati Ilyas; Indah Oktari W (Bajang Institute, 2023)
This study aims to examine the effect between fear of death caused by the covid 19 virus and institutional ownership on herding behavior in companies listed on the LQ45 index (JSII) in the period from 2019 to 2021. The fear variable with the GFI index is a variable that has never been used before by previous studies to be a variable that can estimate whether fear can affect herding behavior. The sample of this study is companies listed on the LQ45 Index on the IDX from 2019 to 2021. The analysis method used is multiple linear regression assisted by Eviews in data processing. The results showed that the fear associated with the global mortality index was able to influence the occurrence of herding behavior on the LQ45 index. Meanwhile, the role of institutional ownership in companies on the IDX is unable to influence the occurrence of herding behavior. This study also proved that at the end of the year and the beginning of 2020 (honeymoon phase) using rolling window regression. It is proved that there has been a herding behavior caused by the fear of investors.